Precision Medicine in Hormone Receptor-Positive Breast Cancer - Nasrazadani, Azadeh; Thomas, Roby A.; Oesterreich, Steffi; Lee, Adrian V. (Frontiers in Oncology, 2018)
In recent decades, breast cancer has become largely manageable due to successes with hormone receptor targeting. Hormone receptor positive tumors have favorable outcomes in comparison to estrogen receptor (ESR1, ER)/progesterone receptor (PR) negative tumors given the targetable nature of these tumors, as well as their inherently less aggressive character. Nonetheless, treatment resistance is frequently encountered due to a variety of mechanisms, including ESR1 mutations and loss of ER expression. A new era of precision medicine utilizes a range of methodologies to allow real time analysis of individual genomic signatures in metastases and liquid biopsies with the goal of finding clinically actionable targets. Preliminary studies have shown improved progression free survival (PFS) and overall survival (OS) with implementation of this information for clinical decision making. In this review, we will discuss the opportunities and challenges in integrating precision medicine through next generation genomic sequencing into the management of breast cancer.